2017
DOI: 10.1074/jbc.m117.785170
|View full text |Cite
|
Sign up to set email alerts
|

The p90 ribosomal S6 kinase–UBR5 pathway controls Toll-like receptor signaling via miRNA-induced translational inhibition of tumor necrosis factor receptor–associated factor 3

Abstract: MicroRNAs (miRNAs) are small, noncodingRNAs that post-transcriptionally regulate gene expression. For example, miRNAs repress gene expression by recruiting the miRNA-induced silencing complex (miRISC), a ribonucleoprotein complex that contains miRNA-engaged Argonaute (Ago) and the scaffold protein GW182. Recently, ubiquitin protein ligase E3 component N-recognin 5 (UBR5) has been identified as a component of miRISC. UBR5 directly interacts with GW182 proteins and participates in miRNA silencing by recruiting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…for gene TRAF3) (Cho et al . ). However, UBR5 has also been shown to ubiquitinylate Groucho/TLE, comprising repressors of transcription, and thus subsequently activate transcription of Armadillo/β‐catenin (Flack et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…for gene TRAF3) (Cho et al . ). However, UBR5 has also been shown to ubiquitinylate Groucho/TLE, comprising repressors of transcription, and thus subsequently activate transcription of Armadillo/β‐catenin (Flack et al .…”
Section: Discussionmentioning
confidence: 97%
“…Other studies also suggest that the protein activity of UBR5 was important, as a result of phosphorylation by p90RSK (Cho et al . ) and mitogen‐activated protein kinase 1 [extracellular signal regulated kinase (ERK)2] in cells in response to epidermal growth factor (Eblen et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a similar observation of no increase in gene expression but increases at the protein level occurred during human muscle cell differentiation. Previous studies have suggested UBR5 translocates into the nucleus in a complex that can silence transcription, for example the gene TRAF3 (Cho et al, 2017). However, has also been shown to ubiquitinylate Groucho/TLE's that are repressors of transcription and thus subsequently activate transcription of Armadillo/β-catenin (Flack et al, 2017).…”
Section: Ubr5 In Atrophy and Recovery From Atrophymentioning
confidence: 99%